Assistência social: os paradoxos de um direito - Raphael, Samira Leinko Matsuda (2018)
The present work seeks to understand the meanings of the Social Assistance Policy (SP) for users residing in the municipality of Itaquaquecetuba - SP from their own lenses and experiences. He sought to understand who these users are, what place they occupy in capitalist society, what paths they take and the challenges they face in order to realize their rights. It briefly presents a socio-historical debate on the formation of the State and its political form, the social question and the development of social policies in capitalism. It analyzes the foundations for the understanding of Law in bourgeois civil society, in this sense it presents a critique of the law subjecting it to the totality of social relations and contributes to the understanding of the Law phenomenon as a socio-historical construction. She sought to discuss social protection in Brazil from the 1930s, in an attempt to understand the institutionalization of Social Assistance as public policy and the contours that it assumes in the current Brazilian context, questioning its advances and contradictions. It emphasizes the conservative practices under the robes of assistance and political clientelism, as a form of access and concession to public goods and services, it points out that this pattern of urban and modern cultural behavior is not exclusive to the Social Assistance Policy, but rather pervades in a peculiar way all social policies. The research is qualitative in nature and, through interviews, the users of social assistance were heard to analyze the meanings they attribute to this policy. Even with all the democratic advance of the Social Assistance Policy, there is a conservative project in the municipality of Itaquaquecetuba -SP, represented by the personal relations of power and exchange of favors, which together with the neoliberal project of characteristics of reduction of the role of the State and social rights prevent the implementation of Social Assistance as public policy and law